Metacriticism, Concept and Mechanisms. - BENSOUIKI, Yamina (Journal of Human Sciences, 2020)
Treating metacriticism nowadays represents a virgin field within contemporary Arab critical discourse. At a time when, thinking about what has been achieved so far, the reader notices that it is characterized by two aspects: -The first resides in the fact that there is a terrible lack of works of metacriticism, -The second finds its explanation in the ambiguity of vision among some researchers in the field of metacriticism. This therefore pushes the reader to ask himself questions more like: -what is the true concept of metacriticism? - What is the difference between criticism and metacritic! - Is it possible to define the mechanisms of metacriticism as was the case for critical methods!Our present study therefore aims to provide clarifications and answers to the various questions raised above, based on the specialized documentation in our possession.